Is earlier better for melanoma checkpoint blockade?. (November 2018) - Robert, Caroline
Abstract A neoadjuvant approach relying on the administration of combined anti-CTLA-4–anti-PD-1 treatment before lymph node surgery is evaluated in two phase 1 trials. Encouraging clinical, pathological and immunological responses to neoadjuvant therapy were observed, suggesting that this concept warrants further exploration; however, any future approach must address the unacceptably high toxicity of the regimens evaluated in these trials.